(untitled) (Transport systems and technologies, 2019)
The aim of the research is to improve the maintenance system of a traction motor (TM) ED-118A by predicting the life of frame insulation and determining recovery moments while ensuring the lowest unit costs for performing major repairs of volume 1 (MjR-1) and permanent repair of volume 3 (PR-3), taking into account the degree of recovery, using data on the insulation state by the return voltage method operation. In the research , the optimization of the unit costs for the overhaul of the MjR-1 and the repair of the PR-3 to restore the insulation properties, with restrictions on the value of the return voltage and the insulation mileage to MjR‑2, taking into account the degree of restoration when performing the PR‑3 and MjR-1. A method is proposed for predicting the life of frame insulation and determining moments of its recovery, taking into account the recovery factor when performing PR‑3 and performing MjR‑1 and data on observations of the return voltage. Researches were carried out in accordance with the “State Program for the Strategic Development of Ukrainian Railways”, prepared by the State Research Center for Railway Transport of Ukraine in conjunction with Ukrzaliznytsya specialists and the Program for the renewal of railway rolling stock for the period up to 2020, where indicated by need for creation of modern systems maintenance and repair of traction rolling stock of a new generation and the development of appropriate regulatory documents.